2022
DOI: 10.1017/s0007485322000104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between window traps and pan traps in monitoring flower-visiting insects in agricultural fields

Abstract: Sampling flower-visiting insects in agricultural fields at large spatial and temporal scales is significant for understanding local insect pollinator communities. The most commonly used method, pan trap, has been criticized due to its attractant bias. A window trap (also referred to as the flight-intercept trap) is a non-attractant sampling method, which has been applied in forests and grasslands, but rarely in agricultural fields. We aim to test whether we can replace pan traps with window traps in agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Our results suggested that both FITs and PTs are surprisingly similar in their per-cost effectiveness and coverage in trapping pollinators. Results showed that a single FIT caught more individuals and species than single PTs, agreeing with the prior study (Rubene et al, 2015;Shi et al, 2022b). It seems likely that the highly attractive oilseed rape reduces the catches of PTs, so nonattractant FITs are less impacted by this and collect more specimens per unit (Baum and Wallen, 2011;Vrdoljak and Samways, 2012;Prendergast et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results suggested that both FITs and PTs are surprisingly similar in their per-cost effectiveness and coverage in trapping pollinators. Results showed that a single FIT caught more individuals and species than single PTs, agreeing with the prior study (Rubene et al, 2015;Shi et al, 2022b). It seems likely that the highly attractive oilseed rape reduces the catches of PTs, so nonattractant FITs are less impacted by this and collect more specimens per unit (Baum and Wallen, 2011;Vrdoljak and Samways, 2012;Prendergast et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Despite much prior research on the topic, there remain many gaps in our knowledge of effective monitoring for pollinating insects, especially in subtropical environments of Asia and for the multitude of passive trap methods (Cane et al, 2000;Campbell and Hanula, 2007;González et al, 2020;Van Drunen et al, 2022). The sampling performance of FITs and PTs, as two common passive pollinator sampling methods, has been assessed at limited scales (one oilseed rape field) previously and found flight interception trap outperform pan trap (more individuals and species collected per trap; Shi et al, 2022b). Here, we expanded on prior efforts by expanding sampling coverage and incorporating trait and semi-natural area analyses to determine whether these factors introduce biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pan, Malaise and vane traps), visual observation and active survey techniques (e.g. sweep netting; Gervais et al, 2018; Kearns & Inouye, 1993; Prado et al, 2017; Shi et al, 2022). Indeed, pan, Malaise and vane traps are some of the most commonly used methods to measure bee diversity in agroecosystems, largely because they provide a low‐cost means to sample multiple sites simultaneously (McCravy, 2018; Prado et al, 2017; Spafford & Lortie, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using these passive survey methods have, for example, demonstrated the benefit of adjacent natural habitats for pollinator abundance and crop yield (see Klein et al, 2012; Morandin & Winston, 2006), and identified the inverse relationship between cultivated land use and wild pollinator diversity, particularly for wild bee species (see Bergholz et al, 2022; Zou et al, 2017). Unfortunately, passive sampling techniques often require extensive time commitments and increasingly rare specialist taxonomic expertise to morphologically identify the arthropod taxa collected or observed (Brown, 2020; Pardo & Borges, 2020; Shi et al, 2022). Furthermore, even when morphological identifications are possible, passive sampling techniques often have intrinsic biases in the taxa that are captured.…”
Section: Introductionmentioning
confidence: 99%